Varicocele: a Case Report - Iqlima Sekar P; Evredy; Naura Shalsabila M; Lia Deska Debora; Ray Sebastian S; Orianne Keisha; Annisa Firdausi; Muhammad Fajar; Keisha Adifa; Mathias Rusli; Wawan Kustiawan (Medical Clinical Update, 2023)
Varicocele is a condition with abnormality in growth and dilatation of veins that drains blood from the testicle, the scrotal venous pampiniform plexus. Although commonly painless, varicocele is the most prevalent cause that resulted in low count of sperm, poor sperm morphology, abnormal analysis of semen, and reduced sperm motility.